2007
DOI: 10.1074/jbc.m705517200
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures of Yeast β-Alanine Synthase Complexes Reveal the Mode of Substrate Binding and Large Scale Domain Closure Movements

Abstract: ␤-Alanine synthase is the final enzyme of the reductive pyrimidine catabolic pathway, which is responsible for the breakdown of uracil and thymine in higher organisms. The fold of the homodimeric enzyme from the yeast Saccharomyces kluyveri identifies it as a member of the AcyI/M20 family of metallopeptidases. Its subunit consists of a catalytic domain harboring a di-zinc center and a smaller dimerization domain. The present site-directed mutagenesis studies identify Glu 159 and Arg 322 as crucial for catalysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
5
27
0
Order By: Relevance
“…None of the mutants showed activity using the standard assay, although only the lysine mutant enzyme secondary structure elements were unaltered when analyzed by far-UV circular dichroism (data not shown). The R291K mutation suggests how essential this residue is in substrate binding, supporting previous results found for other enzymes (19,24).…”
Section: Effects Of Chemical Agents and Metal Ionssupporting
confidence: 76%
See 2 more Smart Citations
“…None of the mutants showed activity using the standard assay, although only the lysine mutant enzyme secondary structure elements were unaltered when analyzed by far-UV circular dichroism (data not shown). The R291K mutation suggests how essential this residue is in substrate binding, supporting previous results found for other enzymes (19,24).…”
Section: Effects Of Chemical Agents and Metal Ionssupporting
confidence: 76%
“…The ␤car At model was obtained by the Swiss-Model server (34), using the substrate-bound structure of Saccharomyces kluyveri NC␤AA (Sk␤as) (PDB accession no. 2V8H_A), which has been solved at 2.0 Å, as a template (19). The stereochemical geometry of the final model was validated by PROCHECK (16) and WHATCHECK (13), included in the model assessment tools of the Swiss-Model server.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unexpectedly, a highly conserved arginine in L-carbamoylases has been proved critical for the dimerization of the enzyme, and thus for enzymatic activity. Comparative studies revealed striking characteristics of the different "dimerization" domains of the peptidase M20/M25/ M40 family, in agreement with previous evolutionary hypotheses on this family of enzymes (3,37) and suggesting new evolutionary considerations. Finally, an alternative reaction mechanism dependent on only one metal atom can be inferred from the experimental data.…”
supporting
confidence: 72%
“…In fact, the Arg and His residues are strictly conserved. Based on the literature available for homologous enzymes, the conserved Arg residue is or might be necessary for substrate binding in ␤-alanine synthase (4,37,38), EcAam (2), peptidase V (PepV) (31), carnosinase (55), IAA-amino acid hydrolase homolog 2 (ILL2) (7), peptidase D (PepD) (9), DapE (46), hAcy1 (35), peptidase T (PepT) (6,24), and metallopeptidase (Sapep) (20). Several homologous structures present different molecules bound to these residues, namely, the structures under PDB IDs 1VIX, 1FNO, 3IC1, 3IFE, and 2QYV.…”
Section: R369 H219(a) N260(a)mentioning
confidence: 99%